ANALISIS KECERDASAN NATURALIS PADA SISWA DI DESA PLADEN - Pangesti, Windi Desiana; Fakhriyah, Fina; Kuryanto, M Syaffruddin (Journal Prakarsa Paedagogia, 2022)
The research is a descriptive qualitative research. The purpose of the research to describe the naturalist intelligence of students in Pladen Village and describe the factors that influence students' naturalist intelligence. The informants in this research were six students in Pladen Village. This research uses data collection techniques including the stages of observation, interviews, and documentation. The results showed that the naturalist intelligence of students in Pladen Village was mostly good in responding to nature (animals, plants, and natural materials). There is still a habit of not caring about plants. There are factors that influence health and the biggest influence is the student's environment.